Thermal analysis in Stokes' second problem of nanofluid: Applications in thermal engineering. (September 2018) - Khan, Ilyas; Abro, Kashif Ali; Mirbhar, M.N.; Tlili, I.
Abstract: Present study is prepared to analyze the heat transfer for the Stokes' second problem of nanofluid. Water is taken as base fluid and two types of nanoparticles namely copper ( C u ) and silver ( A g ) are suspended in it. Exact solutions for velocity field and temperature distribution have been investigated by utilizing the Laplace transform method and presented in the form simple elementary functions. The results lead to the few facts regarding the effects of rheological and pertinent parameters on the graphical illustrations. Heat transfer is decreased with increasing nanoparticles volume fraction. Hartman number and porosity have opposite effects on fluid motion. This study has several applications in thermal engineering.